People living with HIV AIDS (PLWHA) in Batujajar public health center: Improving quality of life through adherence antiretroviral treatment “Antreat ARV” program - Ami Kamila; Anzar Ismail; Hani Nurani Permani (BKM Public Health and Community Medicine, 2021)
One of the efforts to improve the quality of life of PLWHA is to maintain ARV therapy. ARV therapy is also the key to the success of HIV/AIDS treatment. Although it is not curative, continuous therapy can inhibit the growth and the spread of the virus in the body of PLWHA. Based on the data from the AIDS Commission of West Bandung Regency, 10% of the total 474 PLWHA in West Bandung Regency lost to follow-up ARVs. Some of the causes of it can be related to Lawrence Green's theory, such as predisposing factors (knowledge, attitudes), enabling factors (access to ARV services, transport costs), and reinforcing factors (boredom, side effects). Therefore, AIDS Commission of West Bandung Regency tried to prevent increased lost follow-up ARVs by conducting an empowerment program for PLWHA through "Antreat ARVs" Program. Antreat ARV Program aims to improve adherence to ARV treatment in PLWHA by providing health assistance through counseling using the brainstorming method, using digital module and video. In West Bandung Regency, this program was first carried out with the initiation of the AIDS Commission itself in collaboration with Health Institutions, on the target of PLWHA who were in the working area of ​​the Batujajar Health Center, West Bandung Regency. This activity positively impacts the adherence of PLWHA to ARV treatment based on the data from the AIDS Commission, which was followed up one month after the activity. This Antreat ARV Program needs to be regularly carried out by increasing health assistance innovation by empowering the PLWHA community as Peer Support Groups as peer educators and motivators and services for PLWHA at the Public Health Centre to facilitate ARV access.